(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article deals with the specifics of the functioning of sensory images in Eric-Emmanuel Schmitt’s novel «The Child of Noah». The author notes that these images show the highest degree of emotional resonance and it is important component of psychopoetics. Based on the position, which was formulated in the research of H. U. Gumbrecht, it emphasizes the impossibility of ignoring the environment, which bases on his presense there. This position is due to the fact, that the sensory perception of the subject world is the main basic mechanism of human’s comprehension. There are sensory images (visual, sound, tactile, olfactory, taste), which build a semantic model of the composition’s world and show the nature of the character, the worldview of the author in the text. The sensory images were viewed as such as outlined by their physicality. They represent a sense of the individual properties of the environment, it often act as a catalyst for the development of action, focus on the psychological dominance of the character, concentrate on plot-forming moments. At the same time, the sensory concepts are subjective, so they are free to interpret. The article found, that tactile and olfactory images play a huge role and create meaningful microfields in the production of the presence in the story. There are sound and visual concepts which model bright musical and visual exphrasis and realized at all levels of the poetics in composition. In addition, due to the modeling sensory images it creates a powerful reader’s emotional resonance.